Diatomite carrier for rapid formation of Aerobic Granular Sludge. Issue 1 (June 2020) - Basri, H F; Anuar, A N; Yuzir, Ali; Halim, Mohd Hakim Ab
Abstract: Aerobic granular sludge (AGS) is a spherical compact sludge that has a lot of advantages such as great settling ability, high biomass level, good shock resistance and ability to withstand high organic loading rate (OLR) and toxic pollutants. However, it still has a major weakness that influences the low global reputation of AGS which is long granulation time. Therefore, a support material called diatomite which known for its unique characteristic is used in this study to speed up the granulation process in a pilot sequencing batch reactor (SBR) for domestic wastewater treatment. The AGS was cultivated in a pilot bioreactor for 30 days and measured for its characteristic. The result indicates fast granulation with 18 days of AGS formation period. Moreover, SEM images shows the present of diatomite in the inner part of the mature granules and proved its function as a nucleation agent that accelerate the aggregation process. The developed granules demonstrate excellent strength and settleability with strength (IC: 17.42%), SVI of 68 mL/g SS and settling velocity (114 m h −1 ) respectively.